Definição de perímetro de proteção de poços para o setor industrial a partir de modelagem numérica do Aquífero Coxilha das Lombas, em Viamão, RS - Formentini, Jéssica (2018)
Protecting underground hydric resources is an action which involves the conservation both of quality and quantity of water for the current and the next generations’ usages. It can happen through an adoption of management and planning measures that seek conservation of systems and suitable ordering of ground usage. Thus, it is guaranteed that activities that are polluting will be not implemented in places that get major vulnerability to contamination of the aquifer. The industrial sector of beverage production demands large volumes of water that meets the required quality required. In the situations the water fountains are underground, the aquifers must have good productivity and hydrochemistry quality so it has its treatment minimized, which leads to reduction of costs on the end product, also, it is adequate to the usage during the industrial process in which the end product is not compromised regarding its demanded quality. The industrial sector we studies is located on the District of Águas Claras, which is located in Viamão, Rio Grande do Sul, Brazil. The main aquifer from this region is the Aquifer Coxilha das Lombas, which belongs to the geomorphological province of Planície Costeira do Estado do Rio Grande do Sul (PCRS – Rio Grande do Sul’s Coastal Plain), which is composed by sedimentary storages of the “lagoon-barrier” type, which representes, at the same time, na important recharge area to the superficial hydric resources of that region. As it is a coastal zone, this area presents many reserve zones, which often present interconnection with the underground systems. This makes our study delimitates the Zona of Contribuição (ZC), a zone which converges the aquifer water to the well, and it defines the Perímetros de Proteção de Poço (PPPs), which are perimeters of punctual protection of the underground area, and they are: the Perímetro Imediato de Proteção Sanitária (PIPS), the Perímetro de Alerta (PA), the Perímetro de Prevenção (PP) and the Perímetro de Contribuição (PC) (in order, the Immediate perimeter of sanitary protection, the Perimeter of, the Perimeter of preservation and the Perimeter of contribution), all of them considered for the food industry, which was used as a case study in the present research. In order to do that, was initially structured a hydrogeological concept model to the Aquifer Coxilha das Lombas on the industrial area, and after that, we performed numerical simulations and flow lines through the softwares MODFLOW and MODPATH (GMS interface). We got the following results: (i) the presence of two aquifer systems (free and semiconfined), which has the underground flow on the NW-SE direction, (ii) the industry uses a recharging area of the aquifer that is 3,4 times bigger than its private area on its maintaining of the productive process, (iii) ZC to the current extraction scenario have na área of about 2.84 km², (iv) PPPs in rate dimensions of: PIPS (radial of 10.0 m), PA (73.5 m x 40.9 m), PP (147.7 m x 47.7 m) and PC (2.84 km²), and (v) it is verified the occurrence of surface water contribution to the underground water capitation.